PENGARUH PENERAPAN STRATEGI CONCEPT MAPPING TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Putri, Dwi Chyntia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This study aimed to analyze the influence of concept mapping strategy towards the learning result students in social science study on the V B grade of SD Negeri 17 Pontianak Kota. This study used an experimental method with Pre-Experimental design form using One-Group Pretest-Posttest Design. The population in this research were 68 students. The samples in this research was V B as a research class. Based on the t-test, the calculation result obtained t test (7,29) > t table (1,699) with significance level Î± = 5% means a significant influence using concept mapping strategy. The value of effect size (ES) is 0.39 with moderate category. It means that concept mapping strategy give a moderate effect to the learning result students in social science study on the V B grade of SD Negeri 17 Pontianak Kota. Keywords: Influence, Concept Mapping Strategy, Learning Result, Social Science